Comparison of fentanyl versus meperidine as supplements to epidural clonidine-bupivacaine in patients with lower limb orthopedic surgery under combined spinal epidural anesthesia. Issue 1 (December 2015) - Yousef, Ayman; Atef, Ashraf; Awais, Waleed
Abstract Background The analgesic and sedative effect of clonidine explain its common use as adjuvant in regional anesthesia, however the hemodynamic instability associated with its neuroaxial administration is the major drawback. Our study hypothesis is to compare the hemodynamic and analgesic effect of epidural fentanyl in comparison to meperidine when added to clonidine in patients undergoing lower limbs orthopedic surgery using combined spinal–epidural anesthesia. Methods One hundred thirty five ASA physical status I or II patients were recruited for lower limb orthopedic surgery. All received 2 mL intrathecal 0.5 % hyperbaric bupivacaine, 10 mL epidural 0.25 % plain bupivacaine, and 1 mL epidural clonidine 2 μg/kg (Clonidine group) and then either 1 ml fentanyl 25 μg (Fentanyl Group) or 1 ml meperidine 25 mg (Meperidine Group). The quality of surgical anesthesia, incidence of hypotension and bradycardia, intra-operative pain assessment, and onset of postoperative pain, sedation scores and side effects in the postoperative period were recorded. Results The 1st analgesic requirement in the postoperative period was significantly prolonged in the meperidine group (p = 0.001). Significant decrease in the mean arterial blood pressure in fentanyl group was at 15, 30, 45, 60 and 90 min (p = 0.035, 0.019, 0.027, 0.032 and 0.039) respectively, significant decrease in meperdine group was at 15 and 30 min (p = 0.038 and 0.043), while in clonidine group a significant decrease was at 15, 30, 45, and 60 min (p = 0.025, 0.028, 0.036 and 0.042) respectively. Among group changes, the mean arterial blood pressure was significantly higher in meperdine group at 30, 45, 60 and 90 min (p = 0.007, 0.015, 0.029 and 0.033) respectively. A significant decrease in the heart rate in fentanyl group at 15, 30 and 45 min (p = 0.035, 0.018 and 0.029), in meperdine group a significant decrease in the heart rate was at 15 min (p = 0.038), while in clonidine group a significant decrease was at 15, and 30 min (p = 0.016 and 0.003) . Among group changes, the heart rate was significantly higher in meperdine group at 30, 45 and 60 min (p = 0.021, 0.017 and 0.011). VAS were significantly lower in meperdine group in comparison to fentanyl and clonidine groups at 2 h, 3 h and 4 h post-operative period (p = 0.024, 0.001 and 0.039). Conclusion The combined administration of epidural clonidine and meperidine provided better intraoperative hemodynamics and prolonged postoperative analgesia than epidural clonidine fentanyl combination in patients undergoing lower limb orthopedic surgery. Trial registration Clinical Trail Registry (Clinicaltrail.gov)NCT 02128451 .